Formation of polyfunctional photocatalytically active layered oxide materials using coordination nitrates REE and alkali metal as precursors - Dryuchko Оleksandr; Bunyakina, Natalia; Shefer Оleksandr; Laktionov Оleksandr; Halai, Vasyl (Academic journal Industrial Machine Building Civil Engineering, 2022)
The information on alkaline coordination nitrates of rare earth elements of the cerium subgroup - precursors of promising modern multifunctional materials - on the conditions of their formation and existence, the nature of chemical bonding, composition, structure, shape of Ln coordination polyhedra, type of ligand coordination, existence of isotype series is generalized. on stoichiometry of structure, structure, the found out characteristic properties. The obtained data are the basis for detection, identification, control of the phase state of processing objects in the preparatory stages in the formation of nanostructured oxide composite systems of lanthanides and transition elements of special purpose, with catalytic and photocatalytic activity, self-cleaning coating with hydrophilic properties; development of various combined methods of their activation